2020
DOI: 10.1186/s12876-020-01346-4
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a new risk score system for non-variceal upper gastrointestinal bleeding

Abstract: Background: Recently, a new international bleeding score was developed to predict 30-day hospital mortality in patients with upper gastrointestinal bleeding (UGIB). However, the efficacy of this newly developed scoring system has not been extensively investigated. We aimed to validate a new scoring system for predicting 30-day mortality in patients with non-variceal UGIB and determine whether a higher score is associated with re-bleeding, length of hospital stay, and endoscopic failure. Methods: A retrospectiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
2
6
0
2
Order By: Relevance
“…Regarding mortality and intervention, GBS was superior to AIMS65, pRS, and T -score. However, GBS showed poor performance for rebleeding, which is similar to a previous study [ 27 ]. As mentioned in the Asian-Pacific Consensus Group guideline 2018 [ 28 ], GBS does not accurately predict rebleeding.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding mortality and intervention, GBS was superior to AIMS65, pRS, and T -score. However, GBS showed poor performance for rebleeding, which is similar to a previous study [ 27 ]. As mentioned in the Asian-Pacific Consensus Group guideline 2018 [ 28 ], GBS does not accurately predict rebleeding.…”
Section: Discussionsupporting
confidence: 90%
“…In our research cohort, GBS showed the best ability to predict the need for ICU admission for elderly patients (Table 6 ). Except for rebleeding (poor accuracy for the elderly group and moderate accuracy for the younger group), GBS showed acceptable performances for both groups (Tables 3 , 4 , 5 ), which is like the results reported by Kim et al [ 26 ]. As mentioned in the Asian-Pacific Consensus Group guideline 2018 [ 17 ], it is challenging for GBS to predict rebleeding accurately.…”
Section: Discussionsupporting
confidence: 85%
“…Fresh hematemesis or melena accompanied with the development of shock (pulse >100 beats/min, systolic blood pressure 100 mmHg) or a drop in haemoglobin concentration >2 g/dL for >24 hours were considered rebleeding. 13 The length of hospital stays was defined as the date of hospital admission to discharge. Finally, all-cause in-hospital mortality is any death occurring during admission within 30 days.…”
Section: Methodsmentioning
confidence: 99%